‘Wat heeft het gelezene ons nu te zeggen?’: Een nieuwtestamentische respons op Van Woudenberg - Os, Arjan van den (Kerk en theologie, 2025)
This article will be a dialogue of a New Testament scholar with René van Woudenberg and his book on the epistemology of reading. First, Van Woudenberg asks legitimate questions to Biblical scholars on epistemology and meaning. Next, using the quotation from Deuteronomy 25:4 in 1 Corinthians 9:9, this contribution will show that the use of the Old Testament in the New Testament creates tension with the principles of authorial intent found in the work of Van Woudenberg. Finally, the influence of history and sin on reading and the view of Van Woudenberg on the sciences are addressed.